REKODYFIKACJA PRAWA CYWILNEGO W POLSCE WOBEC ROZWOJU EUROPEJSKIEGO PRAWA PRYWATNEGO ROZWAŻANIA NA TLE PROJEKTU KSIĘGI I KODEKSU CYWILNEGO - Kaczorowska, Maria (Wydział Prawa i Administracji UAM, 2009)
The subject of this paper is a reform of the Polish Civil Code in the context of contemporary tendencies to unify private law in Europe. In October 2008 the Civil Law Codifying Commission introduced the draft of Book I of the new code. The essential changes proposed in the draft include removal of general clauses of social coexistence principles and social-economic destination of a right, introduction of a reasonableness clause, and - with regards forms of the declaration of will - annulment of the ad, probationem form and introduction of a document form. The authors of the draft refer to the non-binding uniform European principles of private law (PECL and PEL), and draw inspiration from the draft of a Common Frame of Reference (DCFR). Those regulations, prepared at the initiative of the European Union, were meant to create a basis for the introduction of a common European Civil Code for the Member States. That plan has never materialised, mainly because of the lack of legislative competence of the EU in the field of private law.
RECODIFICATION OF CIVIL LAW IN POLAND IN THE FACE OF THE DEVELOPMENT OF EUROPEAN PRIVATE LAW CONSIDERATIONS AGAINST THE BACKGROUND OF THE DRAFT OF BOOK I OF THE CIVIL CODE